New Publications - Altbach, Philip G. (International Higher Education, 2018)
Editor’s note: IHE no longer publishes short book summaries, but rather provides a more comprehensive listing of new books that will be of interest to a higher education audience. We welcome suggestions from readers for books on higher education published especially outside of the United States and United Kingdom. This list was compiled by Edward Choi, graduate assistant at the Center.